Performance of the Voting Organizing Group for the 2019 Election in Sanana District - Abidin Mantoti; Daud M, F Liando; Welly Waworundeng (Journal of Public Administration and Government, 2022)
The research aims to find out and analyze the performance obstacles faced by the Voting Organizing Group (VOG) in the 2019 General Election in Sanana District, Sula Islands Regency. This research uses qualitative research methods with a phenemonological approach. Primary and secondary data were used. The number of informants taken was nine, consisting of two members of the GEC of the Sula Islands Regency, the Chairman of the Election Committee of the 2019 Election Sanana District, the Chairman of the Sanana District Panwas, the Chairman of the Mangon Village VC, and four members of the 2019 Election VOG. The study used performance management theory from Lijan Poltak Sinambela and Sarton Sinambela by taking three indicators, namely training (technical guidance), work motivation, and work discipline. The study's findings indicate that VOG did not perform well in its task of counting votes at polling stations (PS) in the 2019 election. In a number of cases at PS, based on the agreement of the plenary meeting, a recount of votes was carried out at the sub-district level, indicating that a number of PS shifted the vote for both legislative candidates within one party and between political parties. This shows that there is malpractice in the election results at polling stations, the reason being that the duration of vote counting is too long. On the other hand, the administration of election results recorded in the Vote Count Result Certificate (Form Model C1) made many mistakes and was inaccurate. The reason was that there were too many election administration documents at the polling stations, which made VOG tired and unable to concentrate. Inaccurate election results occurred because capacity building through technical guidance was not optimal, there was poor motivation, and work discipline in the form of job distribution among VOG members was not carried out as it should.